(untitled) (Horizontes de Enfermería, 2018)
Th e present study was carried out in the south from Tulcan city, Carchi province. Th e objective was to determine the knowledge and practices of breast self-examination for the early detection of breast cancer in the female population aged 20-64 years old. Research was carried out in this sector since according to statistical data there were 3 deaths due to breast cancer in 2016 in the Tulcán urban parish, so it is among the top 10 causes of mortality in the female population in the sector. A descriptive, qualitative- quantitative and fi eld study was carried out using the survey technique in order to identify the knowledge and practices that the female population has about breast self-examination. When the research was carried out, 24% of the female population did not know what the breast self-examination was, evidencing the lack of knowledge about the importance of this technique. Of the total population who claimed to know about the subject, she performed it erroneously, since 49% did not take the menstrual cycle into account, 35% did not explore the armpit area, 29% said they did not use a mirror for exploration of breasts; while 57% do not practice it for fear of discovering alterations that aff ect their health. In conclusion, knowing and correctly practicing breast self-examination is paramount since it contributes to the prevention or timely detection of abnormalities that may lead to the risk of developing breast cancer.